THE DISCLOSURE OF LIFE EXPERIENCE AND ITS EXPRESSION IN CULTURAL STUDIES PERSPECTIVE - Dwi Retnani Srinarwati (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2018)
One of the key concepts of cultural studies in dealing with "living culture" is the experience and how to articulate it. The articulation of an experience must avoid pure meaning and the addition of excessive analysis. The pattern of interaction, lifestyle, and mind-set observed will bring the ethnographer at the correct level of articulation. In research, cultural studies develop ethnographic methods. Ethnography is a form of socio-cultural research characterized by an in-depth study of the diversity of socio-cultural phenomena of a society. The study was conducted using primary data collection with interview guidelines; research in one or more cases in depth and comparability; data analysis through the interpretation of the function and meaning of thought and action, resulting in the description and analysis verbally. Reality shows that ethnographs often express the experience of "large groups" and reveal less "disadvantaged" parties. Finally a new approach to the research of "new ethnography" is proposed that aims at developing a way of learning and writing that allows the ethnographer to more accurately understand and reveal and articulate the reality of others' lives. New ethnographic practices are often characterized by various strategies, such as collaboration, self-reflexivity, and polvocality. However, coming to its logical conclusion, the new ethnographic search to become a reality for the different realities of life makes one unable to judge between them.